Dynamics of the Estuarine Turbidity Maximum Zone from Landsat-8 Data: The Case of the Maroni River Estuary, French Guiana - Noelia Abascal-Zorrilla; Vincent Vantrepotte; Nicolas Huybrechts; Dat Dinh Ngoc; Edward J. Anthony; Antoine Gardel (Remote Sensing, 2020)
The estuarine turbidity maximum (ETM) zone occurs in river estuaries due to the effects of tidal dynamics, density-driven residual circulation and deposition/erosion of fine sediments. Even though tropical river estuaries contribute proportionally more to the sediment supply of coastal areas, the ETM in them has been hardly studied. In this study, surface suspended particulate matter (SPM) determined from OLI (Operational Land Imager)-Landsat 8images was used to gain a better understanding of the spatio-temporal dynamics of the ETM of the tropical Maroni estuary (located on the Guianas coast, South America). A method to estimate the remotely-sensed ETM location and its spatiotemporal evolution between 2013 and 2019 was developed. Each ETM was defined from an envelope of normalized SPM values > 0.6 calculated from images of the estuary. The results show the influence of the well-marked seasonal river discharge and of tides, especially during the dry season. The ETM is located in the middle estuary during low river-flow conditions, whereas it shifts towards the mouth during high river flow. Neap–spring tidal cycles result in a push of the ETM closer to the mouth under spring-tide conditions or even outside the mouth during the rainy season. An increase in SPM, especially since 2017, coincident with an extension of the ETM, is shown to reflect the periodic influence of mud banks originating from the mouth of the Amazon and migrating along the coast towards the Orinoco (Venezuela). These results demonstrate the advantages of ocean color data in an exploratory study of the spatio-temporal dynamics of the ETM of a tropical estuary, such as that of the Maroni.